Understanding the use of telehealth in the context of the Family Nurse Partnership and other early years home visiting programmes: A rapid review. (November 2022) - Morrison, Kathleen; Hughes, Thomas; Doi, Lawrence
Overview: This rapid review sought to understand the use of telehealth in early parenthood programmes sharing similarities with the Family Nurse Partnership. Methods: A rapid review protocol was developed in accordance with Cochrane Rapid Reviews Methods Guidance. Medline, Cochrane Library, and CINAHL databases were searched. Inclusion criteria were developed using population, intervention, comparator, outcome, study design, and timeframe components. Two reviewers searched, screened, and extracted data. AMSTAR was used for critical appraisal. Results were synthesised narratively. Results: Searches yielded 18 studies out of 881 for inclusion. Findings were identified across seven domains: acceptability and accessibility ; therapeutic relationships ; flexibility offered by telehealth ; participation and engagement ; confidentiality and privacy ; equipment and technical considerations ; and training and support. Conclusion: Telehealth provides unique opportunities to improve access to early years health services for young mothers. However, considerable accessibility barriers remain in the form of connectivity issues, access to appropriate technology, and the acceptability of remote healthcare delivery. This review presents a timely overview of the opportunities and challenges associated with the use of telehealth in early parenthood and family-based programmes.